INCLUSIVE DEVELOPMENT APPROACH FOR REDUCING SOCIAL EXCLUSION IN URBAN AREA: A CASE STUDY OF MARGINAL GROUPS IN KAMPUNG SEMANGGI, SOLO, CENTRAL JAVA - Warsilah, Henny (Jurnal Masyarakat dan Budaya, 2015)
Since the 1980’s the paradigm of development in developing countries, especially in urban areas, has relied on the economic development with economic growth as the main output. This model tends to produce poverty, deprivation, and social exclusion. Social exclusion is a condition, in which individuals, families, and groups in the population do not have the social and political access toward social resources, lack of participation in social activities, and have inadequate living conditions and facilities. This development paradigm has been criticized as it only uses economic indicators and neglects other non-economical aspects. The challenge is to redefine or conceptualize the development in a wider term as a continuum process on a society or a social system led to social inclusion. It is a new approach, which develops an open environment and involves everyone from various backgrounds in the development process. As the development gap between rural and urban areas is getting wider, understanding social inclusion development is a need. Furthermore, President Joko Widodo’s (Jokowi) Nawacita declared that the State must be present among society; therefore, the development should start from the periphery to the centre in order to improve the quality of life, prosperity, and democracy. This paper aims to reconstruct the values of urban development along with the concept of social inclusion in order to increase the quality of life, social relationships, social cohesion, social participation, and social capital in Solo, Central Java. Keywords: social exclusion, social inclusion, inclusive development